Proceedings of the 6th International Symposium on Health Informatics and Bioinformatics 2011
DOI: 10.1109/hibit.2011.6450801
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of pharmacists towards e-pharmacy application: A work in progress research on medula project

Abstract: In Turkey, there have been a number of projects conducted to provide health services by information and communication technologies (ICT). The aim of these projects is to provide health services in the best form and establishing a network among patients and health foundations. Although these systems provide useful functionalities in theory, they have been frequently questioned for user acceptance of these functionalities in practice. In this study, a web-based application which is used by pharmacists named as M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The initial outcome of the study was that, after the prior study on adoption of the system [8], the research improved in terms of hypotheses, model structure, survey context and semantics. As a result, in this paper, a new model (P-TAM) for assessing user adoption of a HIS was proposed and investigated for the next phase of analysis: Structural Equation Modeling (SEM).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The initial outcome of the study was that, after the prior study on adoption of the system [8], the research improved in terms of hypotheses, model structure, survey context and semantics. As a result, in this paper, a new model (P-TAM) for assessing user adoption of a HIS was proposed and investigated for the next phase of analysis: Structural Equation Modeling (SEM).…”
Section: Discussionmentioning
confidence: 98%
“…However, the duration of the system use may vary based on their experiences. The prior study (Sezgin, et al, 2011) revealed that collecting data from the same region/province may be insufficient about understanding user expectations from the system. Thus, in order to increase representativeness of population, samples were composed of pharmacists from different cities around Turkey.…”
Section: Determining Target Sample and Data Collectionmentioning
confidence: 95%
See 2 more Smart Citations